Effect of dietary probiotic supplementation on biochemical profile of Murrah buffalo calves - Singh, Naman; jain, Aklank; Roy, Biswajit; Thakur, Mohan Singh (Indian Journal of Animal Production and Management, 2017)
The study was conducted at Livestock Farm Adhartal, NDVSU, Jabalpur for a period of three months. A total of 18 murrah buffalo calves of both sexes just after colostrum feeding were selected and divided into 3 groups on the basis of their body weight. Group 1 (control) was fed with the basal ration. Group 2 (T1) was fed with the basal ration with probiotic (Saccharomyces cerevisiae) @5g/animal/day and group 3 (T2) was fed with the basal ration with probiotic (Saccharomyces cerevisiae+ Lactobacillus sporogenes) @ 5g/animal/day. The present study indicated that the total serum protein was significantly (p<0.05) lower in control animals (7.46 g/dl) in comparison to T1 (8.76 g/dl) and T2 (8.50 g/dl) animals. However, no significant difference was observed between T1 and T2. The serum albumin concentration varied significantly (p<0.05) varied among different groups. Highest concentration was observed in T2 group (3.71 g/dl) and lowest value observed in control group (3.53 g/dl). The globulin concentrations also varied significantly (p<0.05) among the experimental groups. Highest value was observed in the T1 group (5.15 g/dl). The highest A:G ratio was observed in T2 group. Serum glucose level differed significantly (p<0.05) among the experimental groups. The mean cholesterol values in all the experimental groups were 80.02±1.38, 66.33±1.40 and 71.41±1.16 mg/dl, respectively for the Control, T1 and T2 groups. The results indicated that there was significantly (p<0.05) lower cholesterol concentration in the probiotic fed group as compared to control group. Further, the calves under T1 group had lower serum cholesterol concentration than in the calves of T2. From the study it can be concluded that the total serum protein and blood glucose concentration could be elevated by supplementation of probiotic in buffalo calves. Since the probiotic has anticholesteroleamic effect the cholesterol was lower in probiotic fed group as compare the non fed group.